(3MdjI GdCHQGQ heG jXgQ efgG ef GdeYGQa hGdCMhGds - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s ((3edWjI HHdGO GdQhe s)
(3ChdgG (B:s
(3jHOC HaUd ai GdMce fJjLI GdMceI hGdYde fJjLI GdeYQaI s
(3BNQgG (B:s
(3eG Hjf UeJ hEYJRGd OGFe hGdLQY hGdSgQ GdfRjg GdYGdi hGddg jhabfG hEjGce dESJYeGd gPg GdGQcGf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B688s
Keywords: (3GdJUha hGdBOGH GdTQYjIs